‘No one blames men in our society’: Indian police officers’ perceptions of female complainants - Tripathi, Saumya (The British journal of criminology, 2021)
The purpose of this study was to identify Indian police officers’ perceptions of female complainants and how these perceptions influenced their handling of cases involving women and girls. Using a phenomenological approach, we conducted a qualitative study involving interviews with 12 police officers who were recruited through purposive and snowball sampling. Patriarchal perceptions regarding gender roles influenced police attitudes regarding female complainants, including scepticism regarding the truthfulness of female complainants. As a result, they often did not file their cases in attempt to prevent women from experiencing shame and social stigma. The study expands our understanding of how the gendered nature of policing has direct implications for the outcomes of complaints made by women in India.